Comparison of atmospheric nitrous acid during severe haze and clean periods in Beijing, China. (January 2016) - Hou, Siqi; Tong, Shengrui; Ge, Maofa; An, Junling
Abstract: Continuous measurements were made in Beijing from 22 February to 2 March in 2014, including a severe haze period and a relatively clean period. The concentration of nitrous acid (HONO) ranged from 0.49 to 3.24 ppbv in the severe haze period and from 0.28 to 1.52 ppbv in the clean period. Daytime mean concentrations of SO2, NO, NO2, and NOx in the severe haze period were 58.7 ppbv, 23.2 ppbv, 48.0 ppbv, 71.2 ppbv, respectively, much higher than those in the clean period. The diurnal variations of HONO, NO, NO2, and NOx were weaker in the severe haze period, whereas O3 diurnal variations were opposite with other species in both periods. Moreover, we found better correlations between HONO and NO2 in the clean period than in the severe haze period. Besides, good correlations between HONO and PM2.5, and between PM2.5 and HONO/NO2 ratio were found when PM2.5 concentrations were <350 μg m −3 . When PM2.5 concentrations were >350 μg m −3, HONO remained nearly invariable, with a value of 2.95 ppbv. Additionally, very good correlations between HONO and RH (R 2 = 0.839), and between HONO/NO2 ratio and RH (R 2 = 0.508) were found when RH was ≤65%. The calculated daytime average unknown HONO source rate was 1.85 ppbv h −1 in the severe haze period, higher than 1.26 ppbv h −1 in the clean period. Highlights: The HONO concentration ranged from 0.49 to 3.24 ppbv in the severe haze period. HONO remained nearly invariable (2.95 ppbv) when PM2.5 concentrations >350 μg m −3 . Daytime Punknown of HONO in the severe haze period was 1.85 ppbv h −1 .